2018
DOI: 10.1021/acs.est.8b02776
|View full text |Cite
|
Sign up to set email alerts
|

Ingested Micronizing Plastic Particle Compositions and Size Distributions within Stranded Post-Hatchling Sea Turtles

Abstract: From July 2015 to November 2016, 96 post-hatchling sea turtles were collected from 118 km of the Atlantic coastline in Florida, USA, including loggerhead, green, and hawksbill sea turtle species. Forty-five of the recovered turtles were rehabilitated and released, but the remaining 52 died and were frozen. At necropsy, the gastrointestinal tracts of most the turtles contained visible plastic, and collected particles of 27 individuals were chemically characterized by Raman microscopy as polyethylene, polypropyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 68 publications
3
34
0
Order By: Relevance
“…The polymers identified through FT-IR analysis reflect the recently reported polymer diversity globally described for microplastics (Gago et al, 2018). PE and polypropylene (PP) are some of the most abundant polymers found as pollutants worldwide (Gago et al, 2018;White et al, 2018). Furthermore, | 747 applications such as encapsulation (Labriola, Mathiowitz, & Darling, 2017).…”
Section: Microplastic Polymer Identificationsupporting
confidence: 54%
See 2 more Smart Citations
“…The polymers identified through FT-IR analysis reflect the recently reported polymer diversity globally described for microplastics (Gago et al, 2018). PE and polypropylene (PP) are some of the most abundant polymers found as pollutants worldwide (Gago et al, 2018;White et al, 2018). Furthermore, | 747 applications such as encapsulation (Labriola, Mathiowitz, & Darling, 2017).…”
Section: Microplastic Polymer Identificationsupporting
confidence: 54%
“…The polymers identified through FT‐IR analysis reflect the recently reported polymer diversity globally described for microplastics (Gago et al, ). PE and polypropylene (PP) are some of the most abundant polymers found as pollutants worldwide (Gago et al, ; White et al, ). Furthermore, Suaria et al () identified 16 classes of synthetic material from the surface waters of the central‐western Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroplastic ingestion is ranked at the same level as other anthropogenic pressures such as by-catch [ 112 ]. The risk of plastic ingestion has been documented for decades and has affected different age groups of sea turtles [ 113 115 ]. As a result, in post hatchlings and juvenile turtles, gastrointestinal impaction or injury directly affect the health and reduced nutrient intake or abnormal buoyancy indirectly impair the fitness [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…The risk of plastic ingestion has been documented for decades and has affected different age groups of sea turtles [ 113 115 ]. As a result, in post hatchlings and juvenile turtles, gastrointestinal impaction or injury directly affect the health and reduced nutrient intake or abnormal buoyancy indirectly impair the fitness [ 113 ]. Generally, the risk of macroplastic ingestion is documented more than microplastics and in some cases is reported to have higher impacts.…”
Section: Resultsmentioning
confidence: 99%